PROPOSED WAREHOUSE LAYOUT AND PROCESSES EVALUATION - Ayu, Ketut Gita (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
The main objective of the study is to implement a variety of tools necessary for the design of an effectiveness warehouse for company X. The first two phases (warehouse activity profiling and warehouse design) are finished. The proposed warehouse design for company X has two floors, which are ground floor and mezzanine. Bin-shelving area, pallet and floor storage area, shipping area, and receiving area are put in the ground floor. The pallet and floor storage area is further divided into four zones: Pallet rack, Floor storage zone, Special pallet zone, and Heavy pallet zone. The shipping area of 4,784 square feet will have five shipping doors which includes the staging area in front of the docks. The receiving area requires approximately 4,000 ft2. Class C SKUs according to viscosity will be put in the mezzanine area which utilizes the vertical space of the building. This area is accessible from forklifts using a spiral corridor close to the receiving area. The warehouse processes will include batch order picking in improving labor hour utilization and high viscosity SKUS shall be placed in the most convenient location of the warehouse.